Contemporary Tendencies of Chronic Rheumatic Heart Disease - Rizamuxamedova M.Z.; Shiranova Sh.A. (Periodica Journal, 2022)
Rheumatic fever is a systemic inflammatory disease of the connective tissue, the process of which is located in the cardiovascular system, develops in connection with group A b- hemolytic streptococcal (ABGS) infection, occurs mainly in children (7-15 years) and inclined young people. V.D. Belyakov's epidemiological analysis shows that ABGS infection appeared at the end of the 20th century and continues to increase as in the previous periods. His analysis made the following prediction: “We are entering the 21st century, and according to the laws of life of streptococcal infection, as in the first half of the twentieth century, it must show its power. In the near future, we will face a highly virulent aggressive ABGS infection, just as powerful as in the early twentieth century. ” This prognosis suggests that with the increase in the epidemic “outbreak” of acute respiratory infection (ARI) in the United States and Western Europe, the incidence of ABGS infection is increasing, even fatal. ARI and chronic rheumatic heart disease (CRHD) are the main cardiovascular diseases for which prevention can be sufficiently effective.
Keywords: Rheumatic; infection; streptococcus; epidemiology